Pemberdayaan Komunitas Anak Jalanan Yogyakarta Melalui Bermain Peran - Fatwa Tentama; Dessy Pranungsari; Nissa Tarnoto (Universitas Mathla'ul Anwar Banten, 2017)
For an optimal development of the child's mother in every aspect of its development is very important. One aspect of skills that must be developed from an early age is a social skill. Most of the streets are young mothers of young children in Yogyakarta worried with the development of their social skills. The young mother does not know how to provide the appropriate stimulation to the child, especially to teach children social skills. Stimulate the child's development of social skills of children aspect then held a training play a role to the street children and of young mothers streets. Training was conducted for two days with story, discussions and role play. The purpose of this training is to improve the social skills of children so that they can adapt to their social environment. The results of the training is role playing a child's social skills to be increased after the training given by the method of playing the role. Social skills of children who increasingly include socializing in the neighborhood play when new friends, increase vocabulary, follow the rules of the game, and resolve conflicts with peers.